PENGARUH KECERDASAN EMOSIONAL DAN EFIKASI DIRI TERHADAP ACTIVE COPING DI PT. AUTO HONDA RANGKASBITUNG - Wildan Wildan; Andhika Oktaviani Putri (The Asia Pacific Journal Of Management Studies, 2018)
Purpose-This study seeks to draw on the theories of personality to investigate antecedents and outcomes of consumer coping in instances of service failure. Specifically, the authors focus on the effects of emotional intelligence and self-efficacy on three coping strategies – active, expressive, and denial. The authors further investigate the effects of coping strategies on consumer intention to complainDesign/methodology/approach – An online panel of 51 respondents representative of the Australian population participated in this study. Structural equation modelling was used to analyze data and test hypothesized relationships.Findings – Emotional intelligence has a positive association with active and expressive coping strategies but a negative relationship with denial. Expressive coping leads to greater complaining, whereas denial decreases it. Furthermore, consumer self-efficacy mediates the relationship between emotional intelligence and Active Coping strategy. In contrast, the effect of self-efficacy on expressive strategy is negative.Research limitations/implications – This study is the first step in investigating relationships between consumer emotional intelligence, self-efficacy and coping. The authors also investigate which coping strategies facilitate or hinder consumers’ decisions to complain. Future research should extend the model to incorporate service provider responses to gain a better understanding of the customer coping process in service failures.Originality/value – The paper contributes to the theory of consumer coping by bridging the current research gap and focusing on antecedents and outcomes of coping. This study advances knowledge of consumer coping by examining consumer emotional intelligence and self-efficacy as antecedents of coping strategies. Complaining behaviour is examined as an extension of coping strategies.